AYUDAA.. .a) f(x)= x al cubo f(x + ∆x) -f(x) entre ∆x

b) f(x)= 3x - 1 f(x)- f(1) entre x- 1

c) f(x) 1 entre raiz x- 1 f(x)-f(2) entre x-2

d) f(x) = x al cubo - x f(x)-f(1) entre x-1

e) limx -> 2 x a la 4

f) limx-> -2 x al cubo

g) lim x-> 0 (2x-1)

h) lim x->-3 (3x+2)

i) limx->-3 (x al cuadrado +3x)

j) limx->1 (-x al cuadrado + 1)

k) limx->-3 (2x al cuadrado +4x+1)

l) limx->1 (3x al cubo - 2x al cuadrado +4)

m) lim x->2 1 entre x

n) lim x->-3 2 entre x +2

o) limx->1 x-3 entre x al cuadrado +4

. p) limx->3 2x-3 entre x+5

q) lim-x>3 raiz de x+1

r) limx->4 cubo de raiz x +4

s) limx-> -4 (x+3) al cuadrado

t) lim x->0 (2x-1) al cubo

1

Respuestas

2013-03-27T04:04:02+01:00